Multivesicular release favors short term synaptic depression in hippocampal autapses - Martínez San Segundo, Pablo; Terni, Beatrice; Llobet, Artur (Frontiers in Cellular Neuroscience, 2023)
Univesicular and multivesicular synchronous release of neurotransmitters occurs in presynaptic terminals of the central nervous system. Here, we show that the expression of SF-iGluSnFR.S72A in the astrocytic feeder layer of autaptic hippocampal neuronal cultures allows to associate glutamate release to excitatory postsynaptic currents. Electrophysiology and imaging provided comparable readouts of the time course of postsynaptic responses and short-term synaptic plasticity. The presence of the glutamate sensor in glial cells avoided any interference with the function of endogenous postsynaptic receptors. It was possible to optically detect alterations in the probability of neurotransmitter release, which was heterogenous among synaptic boutons studied. Any given neuron possessed a predominant population of presynaptic terminals that displayed univesicular or multivesicular neurotransmitter release. The prevalence of multivesicular release increased synaptic strength and enhanced short-term synaptic depression. These results show that the preference of hippocampal boutons to synchronously release one or more vesicles determines the strength and low pass filtering properties of synapses established.